Evaluation of the Sensitivity and Specificity of the Tuberculosis Sign and Symptom (TBSS) Score in Comparison with Chest Radiography and Rapid Molecular Test for Diagnosing Tuberculosis Among Brick Kiln Workers - Retno Ariza Soemarwoto; Anse Diana Valentiene Messah; Pad Dilangga; Isura Febrihartati (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2024)
Purpose: The aim of this study is to evaluate the sensitivity and specificity of the Tuberculosis Sign and Symptom Score in comparison to chest radiography and rapid molecular testing among brick kiln workers in Pringsewu Regency. Patients and methods: This study uses a cross-sectional design. This study used a total sampling method, with total samples are 92. The study was conducted from February to March 2024 in a brick kiln located in Saribumi Village, Gading Rejo District, Pringsewu Regency, Lampung Province. Results: The sample in this study consists of 92 subjects. The majority of the sample is female, accounting for 77.3%, while males make up 22.8%. The most common age range is 41-60 years, representing 48.9% of the total. In terms of job categories, most workers are employed in the molding section. The screening with TBSS score and chest radiography yielded a sensitivity of 0.25, specificity of 0.93, positive predictive value of 0.14, and negative predictive value of 0.96. The sensitivity and specificity between the RTM test and TB ss score cannot be assessed because the results of the RTM examination showed that all respondents were negative for TB. Conclusion: All sputum examinations using rapid molecular testing (RMT) showed negative results. Its preventing the assessment of sensitivity and specificity for this method. This discrepancy may be due to suboptimal sample quality.